Identifikasi Sektor Katalisator dalam Perekonomian Wilayah Provinsi Sulawesi Utara - Canon, Syarwani (Jurnal Ekonomi dan Pembangunan Indonesia, 2010)
Direct relation model has been known as an analytical model to measure the relationship between economic sectors. However, there has not been known an analysis to measure the catalyst sector. Generally, the analytical model of relations of economic activities is an aggregative model which neglects the function of catalyst sector. Possibly, this will ignore its influence, when sometimes it is important to know the acceleration this influence for planning purposes. This paper uses analytical model of catalyst sectors of nine sectors in North Sulawesi Province with 56 causality combinations in each of the cataiyst sector. The result shows that nine important economy sectors in North Sulawesi Province are induced by three economy catalyst sectors. First, strong catalyst sector consists of transport and communication sector, manufacturing industry sector, and trade, hotel and restaurants sector. Second, medium catalyst sector; consists of agriculture sector, finance, real estate and business services sector, and electricity, gas and water supply sector. Third, weak catalyst sector: consists of construction sector, services sector, and mining and quarrying sector.